2022
DOI: 10.3389/fmicb.2022.968592
|View full text |Cite
|
Sign up to set email alerts
|

Survival characteristics and transcriptome profiling reveal the adaptive response of the Brucella melitensis 16M biofilm to osmotic stress

Abstract: Brucella can inhabit hostile environments, including osmotic stress. How Brucella responds collectively to osmotic stress is largely unexplored, particularly in spatially structured communities such as a biofilm. To gain insight into this growth mode, we set out to characterize the Brucella melitensis 16M biofilm, describe its phenotype, and carry out a comparative transcriptomic analysis between biofilms under osmotic stress and control conditions. We determined that the bacteria challenged with 1.5 M NaCl ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…ABC transporter proteins are crucial for bacterial adaption to salt stress due to reduced molecule absorption, energy consumption, and regulation of osmotic pressure under high salinity conditions ( Liu, J. T. et al, 2022 ). Further, a previous study found that ABC transporter genes were related to the bacterial response to osmotic stress, containing one specific locus that could mediate betaine accumulation to eliminate osmotic stress ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporter proteins are crucial for bacterial adaption to salt stress due to reduced molecule absorption, energy consumption, and regulation of osmotic pressure under high salinity conditions ( Liu, J. T. et al, 2022 ). Further, a previous study found that ABC transporter genes were related to the bacterial response to osmotic stress, containing one specific locus that could mediate betaine accumulation to eliminate osmotic stress ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%